2014
DOI: 10.3389/fmicb.2014.00510
|View full text |Cite
|
Sign up to set email alerts
|

The symbiont side of symbiosis: do microbes really benefit?

Abstract: Microbial associations are integral to all eukaryotes. Mutualism, the interaction of two species for the benefit of both, is an important aspect of microbial associations, with evidence that multicellular organisms in particular benefit from microbes. However, the microbe’s perspective has largely been ignored, and it is unknown whether most microbial symbionts benefit from their associations with hosts. It has been presumed that microbial symbionts receive host-derived nutrients or a competition-free environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 81 publications
0
67
0
Order By: Relevance
“…It has also been suggested that things are not what they seem for the Symbiodinium either. The coral host might be benefiting at the expense of their microbes by capturing and controlling its algal symbionts (Garcia and Gerardo 2014). Wooldridge (2010) suggests that "the coral host exerts a 'controlled parasitism' over its algal symbionts that is akin to an enforced domestication arrangement" with the "…the coral host as an active 'farmer' of the energy-rich photoassimilates from its captive symbionts."…”
Section: The Coral Holobiontmentioning
confidence: 99%
“…It has also been suggested that things are not what they seem for the Symbiodinium either. The coral host might be benefiting at the expense of their microbes by capturing and controlling its algal symbionts (Garcia and Gerardo 2014). Wooldridge (2010) suggests that "the coral host exerts a 'controlled parasitism' over its algal symbionts that is akin to an enforced domestication arrangement" with the "…the coral host as an active 'farmer' of the energy-rich photoassimilates from its captive symbionts."…”
Section: The Coral Holobiontmentioning
confidence: 99%
“…Despite its ecological relevance, symbiont strain diversity is easily overlooked when studied using classical microbiological techniques and canonical sequence analysis pipelines (Eren et al ., ), and a comprehensive view on the prevalence and consequences of multiple infections in symbiotic associations is lacking (Douglas, ; Garcia and Gerardo, ). However, thanks to advances in sequencing technologies and molecular data analysis, tools to investigate microbial diversity at a higher resolution have become readily available (Eren et al ., ; Engel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the highly intimate intracellular symbioses usually exhibiting low symbiont strain diversity or even monoclonal symbionts, extracellular and/or facultative symbiotic associations can be of a more dynamic nature, sometimes involving multiple symbiotic strains within individual hosts (Vautrin and Vavre, 2009;Ferrari and Vavre, 2011;Kikuchi et al, 2011;Engel et al, 2014;Garcia and Gerardo, 2014;Kwong et al, 2014;Powell et al, 2016). The maintenance of multiple coinfecting strains might have considerable impact on symbiotic partnerships, especially since metabolic differences may exist even between closely related strains and could thereby affect functional roles within the host (see for example Engel et al, 2014;Kwong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent relatedness between microbial community composition in the gut and host phylogeny has been interpreted as evidence of coevolution [39]. Symbiotic gut microbes associated with the host are predicted to evolve host-specific traits and, as a result, display enhanced ecological performances in their host [36,40]. To assess evolution and adaptation of L. reuteri strains to different hosts, the gene content of poultry isolates was analyzed together with that of 40 L. reuteri strains available by NCBI, obtained from different hosts: human (6), rat (1), mouse (3), pig (4), sourdough (4), goat (5), sheep (4), cow (4), horse (3) and poultry (6).…”
Section: Comparative Phylogenetic Analysis Of L Reuteri Strains Frommentioning
confidence: 99%